Risk factors of degenerative lumbar scoliosis in patients with lumbar spinal canal stenosis. Issue 38 (September 2019) - Wang, Chunlei; Chang, Hengrui; Gao, Xianda; Xu, Jiaxin; Meng, Xianzhong
Abstract : Abstract: Lumbar spinal canal stenosis (LSCS) associated with degenerative scoliosis has being increasingly aware by the public and studied by many researchers. Degenerative changes leading to spinal stenosis can precede a spinal deformity which will develop into the de novo scoliosis. There are few studies focusing on the risk factors contributing to the degenerative lumbar scoliosis (DLS) in lumbar spinal stenosis patients. From September, 2017 to December, 2017, 181 patients who were diagnosed with LSCS in the outpatient department of our hospital were enrolled in this retrospective investigation. The patients were divided into 2 groups: DLS group (Cobb angle >10°) and LSCS group. Sex, age, smoking status (yes or no), occupation (heavy or light labor), body mass index (BMI), bone mineral density (BMD) and radiographic parameters including the lumbar lordosis (LL), pelvic incidence (PI), pelvic tilt (PT), sacral slope (SS), thoracic kyphosis (TK), coronal vertical axis, and sagittal vertical axis (SVA) are all evaluated as potential risk factors. Multivariate logistic regression analysis and receiver-operating characteristic curves were used to identify potential risk factors. Forty-five of 181 patients were diagnosed with DLS and involved in the DLS group. There were significant differences between the 2 groups in BMI ( P  < .001), LL ( P  = .0046), BMD ( P  < .001), SVA ( P  < .001), and TK ( P  = .047). BMD < −1.85 g/cm 2 (adjusted odds ratio [AOR] 0.030, 95% confidence interval [CI] 0.008–0.107, P  < .001), BMI >25.57 kg/m 2 (AOR 1.270, 95% CI 1.040–1.551, P  = .019), and SVA >3.98 cm (AOR 3.651, 95% CI 2.226–5.990, P  < .001) had good accuracy to predict the formation of degenerative lumbar scoliosis based on degenerative lumbar spinal stenosis. Degenerative lumbar scoliosis has a high incidence in degenerative lumbar spinal stenosis. BMD <−1.85 g/cm 2, BMI >25.57 kg/m 2, and SVA >3.98 cm were the potential risk factors for the formation of degenerative lumbar scoliosis based on degenerative lumbar spinal stenosis.